Developing and testing of collagen coated polylactic-glycolic acid (PLGA)neural conduit - Sulong, Ahmad Fadzli; Hassan, Nur Hidayah; MH, Hazla; Naicker, Amaramalar S.; A, Shalimar; N, Angela; Y, Reusmaazran (2011)
Background Autologous nerve grafts to bridge nerve gaps poses various drawbacks. Nerve tissue engineering to promote nerve regeneration using artificial neural conduits has emerged as a promising alternative. Objective We aim to develop an artificial nerve conduit using collagen-coated polylactic-glycolic acid (PLGA), and analyse the biomechanical properties of the conduit and survivability and propagating ability of the neuro-transdifferentiated human mesenchymal stem cells in this conduit. Methods The PLGA conduit was constructed by dip-molding method and coated with collagen by immersing the conduit in collagen bath. The biomechanical strength and ultra structure of the conduits were examined before they were seeded with as neuro-transdifferentiated human mesenchymal stem cells (ntMSC) and implanted sub-muscularly on nude mice thigh. The non-collagen coated PLGA conduit seeded with ntMSC and non-seeded non-collagen coated PLGA conduit were also implanted for comparison purpose. The survivability and propagation ability of ntMSC was studied by histological and immunohistochemical analysis. Results The collagen coated conduits had smooth inner wall and highly porous outer wall. They also demonstrated good physicomechanical properties, malleability and ability to stretch. Conduits coated with collagen and seeded with ntMSCs produced the most number of cells after 3 weeks. The best conduit based on the number of cells contained within it after 3 weeks was the collagen coated PLGA conduit seeded with neuro-transdifferentiated cells. The collagen coated PLGA conduit found to be suitable for attachment, survival and proliferation of the ntMSC. Minimal cell infiltration was found in the implanted conduits where nearly all of the cells found in the cell seeded conduits are non-mouse origin and have neural cell markers, which exhibits the biocompatibility of the conduits. Conclusion The collagen coated PLGA conduit has adequate physical properties, biocompatible, non-cytotoxic and suitable for use as artificial nerve conduits.